The general aviation handbook - Simpson, Rod (Midland, 2005)
This is a completely new and revised edition of the General Aviation Handbook, long overdue since it has been over 10 years since the last edition was published. This edition is fully revised and updated and contains 10 years worth of updated material, including the addition of a number of manufacturers and aircraft which were omitted from earlier editions for various reasons. Aircraft new to this edition include the so-called "heavy microlights", which are now an important part of the worldwide light aircraft scene. About 90 percent of the photos are new, and larger page size provides greater space for large data tables and photos. Previous editions have been strong sellers; this is the main reference book on this important sector of the aviation world, and this new edition will be welcomed by both aviation enthusiasts and those involved in the aviation industry.